The Influence of Workload and Organizational Culture on Employee Performance with Organizational Learning as A Mediating Variable - Latupapua, Conchita Valentina; Wenno, Meiske; Patty, Martha Racwel (Jurnal Mebis, 2025)
This study aims to examine and analyze the influence of workload and organizational culture on employee performance, with organizational learning as a mediating variable at the Inspectorate Office of Central Maluku Regency. This research adopts a quantitative approach and, based on the level of explanation, is classified as associative research. Data were collected through questionnaires, observations, and documentation, and were analyzed by testing hypotheses and identifying the relationships between variables using path coefficient correction through Smart PLS version 4.0. The results indicate that both workload and organizational culture have a direct, positive, and significant effect on employee performance and organizational learning. Furthermore, organizational learning also has a direct, positive, and significant effect on employee performance. However, organizational learning does not mediate the relationship between workload and employee performance. In contrast, it successfully mediates the relationship between organizational culture and employee performance, with a positive and significant effect at the Inspectorate Office of Central Maluku Regency.